Plasma copeptin as marker of cardiovascular disease in asymptomatic type 2 diabetes patients. (November 2014) - Bar-Shalom, Dana; Poulsen, Mikael K; Rasmussen, Lars M; Diederichsen, Axel CP; Sand, Niels PR; Henriksen, Jan E; Nybo, Mads
Recently, copeptin was found associated with cardiovascular disease (CVD) and all-cause mortality in type 2 diabetes mellitus (T2DM) patients treated in primary care. This study aimed to evaluate whether plasma copeptin correlated to CVD in asymptomatic T2DM patients intensively investigated for sub-clinical CVD. A total of 302 T2DM patients referred to the Diabetes Clinic at Odense University Hospital, Denmark, entered the study. None of the patients had known or suspected CVD. As a control group, 30 healthy adults were recruited from the DanRisk study – a random sample of middle-aged Danes. A variety of clinical investigations were performed, including blood pressure measurements, carotid intima media thickness evaluation and myocardial perfusion scintigraphy. Blood sample analyses included copeptin measurements. Median plasma copeptin concentrations were similar in the T2DM group and the control group. However, men had significantly higher copeptin concentrations than women in the T2DM group (p < 0.001), and also, T2DM men had significantly higher copeptin concentrations than men without T2DM (p = 0.038). Copeptin correlated significantly with a number of variables, but the strongest correlation was with creatinine (R = 0.432, p < 0.001), and in multiple regression analysis, only this correlation remained significant. When association with clinical scores were investigated, plasma copeptin remained significantly associated with peripheral arterial disease (PAD) (p = 0.01). We found correlations between creatinine, copeptin levels and PAD in T2DM patients, and if confirmed, plasma copeptin combined with plasma creatinine could be a candidate for PAD screening in T2DM patients.